Indigeneity and legal pluralism in India : claims, histories, meanings - Parmar, Pooja (Cambridge studies in law and society, 2015)
"As calls for reparations to indigenous peoples grow on every continent, issues around resource extraction and dispossession raise complex legal questions. What do these disputes mean to those affected? How do the narratives of indigenous people, legal professionals, and the media intersect? In this richly layered and nuanced account, Pooja Parmar focuses on indigeneity in the widely publicized controversy over a Coca-Cola bottling facility in Kerala, India. Juxtaposing popular, legal, and Adivasi narratives, Parmar examines how meanings are gained and lost through translation of complex claims into the languages of social movements and formal legal systems. Included are perspectives of the diverse range of actors involved, based on interviews with members of Adivasi communities, social activists, bureaucrats, politicians, lawyers, and judges. Presented in clear, accessible prose, Parmar's account of translation enriches debates in the fields of legal pluralism, indigeneity, and development"--